Selenate Enhances STAT3 Transcriptional Activity in Endothelial Cells: Differential Actions of Selenate and Selenite on LIF Cytokine Signaling and Cell Viability - Alturkmani, Hani J. (2012)
Sodium selenate may have utility in treating Alzheimer’s disease and diabetes; however, its impact on the associated proinflammatory cytokine signaling of endothelial cells has not been investigated. We report that treatment of human microvascular endothelial cells with sodium selenate at a pharmacological dose (100 μM) enhanced tyrosine phosphorylation of nuclear STAT3 on Y705 in response to IL-6-type cytokine, leukemia inhibitory factor (LIF), indicative of enhanced STAT3 activity. Accordingly, STAT3 nuclear binding to DNA was increased, as well as LIF-induced gene expression of chemokine (C-C motif) ligand 2 (CCL2). CCL2 plays a key role in inflammatory processes associated with neuronal degenerative and vascular diseases. The enhancing action of selenate on LIF-induced STAT3 Y705 phosphorylation was replicated by vanadate and a specific inhibitor of protein tyrosine phosphatase, non-receptor type 1 (PTP1B). Moreover, we observed that selenite, the cellular reduction bioproduct of selenate but not selenate itself, inhibited enzymatic activity of human recombinant PTP1B. Our findings support the conclusion that in human microvascular endothelial cells selenate has a vanadate-like effect in inhibiting PTP1B and enhancing proinflammatory STAT3 activation. These findings raise the possibility that beneficial actions of supranutritional levels of selenate for treating Alzheimer’s and diabetes may be offset by a proinflammatory action on endothelial cells.